Peningkatan Kemampuan Literasi Digital dan Membangun Perdamaian bagi Pemuda Kabupaten Ciamis di Era Revolusi Industri 4.0 di Tengah Pandemi Covid-19 - Yuniasih, Tulus; Idroes, Afri Asnelly; Yusran, Yusran; Awal, Syahrul (PT Hakhara Akademia Indonesia, 2024)
This article discusses the community services conducted as the second implementation of cooperation between Universitas Budi Luhur (UBL) and Provincial Government of Ciamis by the International Relations Study Programme of FISIP UBL. The community service aims to solve problems in human resources especially during the pandemic Covid-19. The community service takes form of workshop for digital literacy and peace education for high school and vocational school students. The method covers simulation, ice breaking, and lecturing. Simulation was done through focus group discussion and quizzes, stimulating skills required in building the physical and psychological health in order to face the future. This workshop was attended by 7 (seven) schools, comprising of students and teachers. The result shows that the participants have understood the challenges and opportunities coming from the Industrial Revolution 4.0, especially for the youth to support the Government in building positive communication during the pandemic. The participants have also comprehended steps or ways in facing such challenges and opportunities, by considering the power of digital media in empowering the negotiation position for peace, and by considering the existence of different perspectives and interests in education sector, and by also applying the nobility values and open mind attitude.